Hemp (Cannabis sativa) seed for reproduction of stored-product insects. (May 2021) - Hamilton, Kimberly; White, Noel D.G.; Jian, Fuji; Fields, Paul G.
Abstract: Hemp, or industrial hemp ( Cannabis sativa ), is a high value alternative crop that has seen increases in production in Canada since commercial production was legalized in 1998. Insect infestation of stored hemp seed may result in loss of quality and value. There are few published studies on the ability of insects to survive and reproduce on hemp seed. Reproduction of eleven stored-product insects on hemp seed at different moisture contents with, or without dockage, was studied. Insects were introduced into 15 g of hemp seed at two initial moisture contents (dry, 9% m.c. or damp, 15% m.c.), two dockage levels (dockage-free or dockage, 15%), and held at 30°C and 60–70% r.h. Five replicates of each treatment for each species were used. For beetles, twenty unsexed adults were used, for Ephestia kuehniella (Mediterranean flour moth), twenty eggs were used. For the beetles, live and dead adults were counted after 3, 5, 7 and 9 weeks, for the moth, adults were counted after 12.5 weeks. After counting, only live adults were returned to the hemp seed. The following beetle populations increased over the 9 weeks; Tribolium castaneum (red flour beetle), Lasioderma serricorne (cigarette beetle), Oryzaephilus surinamensis (sawtoothed grain beetle) and Trogoderma variabile (warehouse beetle). The following species did not increase their populations; Cryptolestes ferrugineus (rusty grain beetle), Rhyzopertha dominica (lesser grain borer), Sitophilus oryzae (rice weevil), Cryptolestes turcicus (flour mill beetle), Tribolium confusum (confused flour beetle), and Stegobium paniceum (drugstore beetle). For the beetles, higher dockage generally led to higher populations. The effect of moisture content was variable. Ephestia kuehniella produced adults on all treatments, with the dry treatment containing dockage performing the best. Highlights: Reproduction of 11 stored-product insects on hemp ( Cannabis sativa ) seed tested. L. serricorne, O. surinamensis, T. variabile and T. castaneum populations increased. C. ferrugineus, R. dominica, C. turcicus, T. confusum and S. paniceum populations decreased. Higher dockage generally led to higher populations. The effect of moisture content was variable.